Soil temperature, soil moisture and maize yield from mulched and unmulched tropical soils - Lal, R. (Springer, 1974)
The effect of mulching on maize yield was investigated for luvisol and cambisol tropical soils during 1970–72. The increase in grain yield by mulching was 46, 52 and 22 per cent respectively, for 1970, 1971 and 1972. Mulched plants had higher growth rate and vigour and chlorotic symptoms of nutritional disorders were observed only for unmulched plants. Mulching significantly decreased the maximum soil temperature measured at 5, 10 and 20 cm depths. In the initial stages of crop growth, temperature differences of as much as 8°C were observed between mulched and unmulched plots at a 5-cm depth. Mulched plots also had a higher soil moisture content. Increase in grain yield by mulching was attributed primarily to a decrease in soil temperature and partly to improved soil moisture regime.